2011
DOI: 10.3892/ol.2011.331
|View full text |Cite
|
Sign up to set email alerts
|

p53 regulates the expression of human angiotensin II AT2 receptor interacting protein (ATIP1) gene

Abstract: Angiotensin II AT2 receptor interacting protein 1 (ATIP1) has been recently identified as a tumor suppressor. In the present study, a 2.2 kb fragment of the 5′ flanking region of the human ATIP1 gene was cloned, and its promoter activity was confirmed. Two putative p53 binding sites were identified in the minimal promoter. Cisplatin treatment and ectopic expression of p53 led to enhanced ATIP1 expression. Knockdown of p53 reduced the ATIP1 expression. The direct interaction of p53 and the ATIP1 promoter was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Many genes involved in the control of DNA repair are regulated by p53. The MTUS1 promoter contains two p53 responsive elements [ 22 ]. Our study for the first time showed that TMZ or irradiation of GBM cells induces ATIP1 expression in a p53-dependent manner ( Figure 5 , Figure S7a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many genes involved in the control of DNA repair are regulated by p53. The MTUS1 promoter contains two p53 responsive elements [ 22 ]. Our study for the first time showed that TMZ or irradiation of GBM cells induces ATIP1 expression in a p53-dependent manner ( Figure 5 , Figure S7a ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the important role of maintaining vascular integrity and homeostasis at the level of the angiotensin II (AngII)/angiotensin receptor system (AT x R) through the Renin Angiotensin Aldosterone System (RAAS) [ 20 ], RAAS also plays a crucial role in cancer biology and affects tumor growth by remodeling the tumor microenvironment [ 21 ]. In oral squamous cell carcinoma, ATIP1 is regulated by p53 and inhibits epidermal growth factor (EGF)-mediated ERK phosphorylation, cell proliferation and migration, indicating that ATIP1 serves as a tumor suppressor [ 22 , 23 ]. In the central nervous system (CNS), ATIP1 is the most abundant transcript expressed in all brain regions except the cerebellum and fetal brain and is involved in neural differentiation [ 18 , 24 , 25 ], suggesting that it might play a crucial role in physiological functions via different intracellular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the initial report that MTUS1 may be a candidate tumor suppressor gene in pancreatic cancer [ 1 ], inactivation of the gene in knock-out animals was associated with B cell lymphoproliferative disease [ 17 ]. Furthermore, p53-regulation of ATIP1 transcripts suggested a link between MTUS1 gene regulation and cancer [ 18 ]. Indeed, MTUS1 down-regulation in cancer tissues was frequently reported, including in tumors from the breast [ 19 , 20 , 21 , 22 , 23 ], bladder [ 24 , 25 ], colon [ 26 , 27 , 28 , 29 ], gallbladder [ 30 ], gastric tissues [ 31 , 32 ], lung (NSCLC) [ 33 ], head-and-neck [ 34 , 35 , 36 , 37 , 38 , 39 ], clear cell renal cell carcinoma (cc-RCC) [ 40 , 41 ], and uveal melanoma [ 42 ], with the exception of prostate cancer, in which MTUS1 expression was reported to increase with cancer progression [ 43 , 44 ] ( Table 1 ).…”
Section: Atip3 and The Mtus1 Gene A Historical Point Of Viewmentioning
confidence: 99%
“…Furthermore, high ATIP1 expression might retard the response to radiation therapy by enhancing double-strand DNA break repair [30] . ATIP1 participates in p53-involved tumor signal transduction through binding between the ATIP1 promoter and p53 [31] .…”
Section: Introductionmentioning
confidence: 99%